Transcriptome analysis of the ependymal barrier during murine neurocysticercosis - Mishra Pramod; Teale Judy M (Journal of Neuroinflammation, 2012)
Abstract Background Central nervous system (CNS) barriers play a pivotal role in the protection and homeostasis of the CNS by enabling the exchange of metabolites while restricting the entry of xenobiotics, blood cells and blood-borne macromolecules. While the blood–brain barrier and blood-cerebrospinal fluid barrier (CSF) control the interface between the blood and CNS, the ependyma acts as a barrier between the CSF and parenchyma, and regulates hydrocephalic pressure and metabolic toxicity. Neurocysticercosis (NCC) is an infection of the CNS caused by the metacestode (larva) of Taenia solium and a major cause of acquired epilepsy worldwide. The common clinical manifestations of NCC are seizures, hydrocephalus and symptoms due to increased intracranial pressure. The majority of the associated pathogenesis is attributed to the immune response against the parasite. The properties of the CNS barriers, including the ependyma, are affected during infection, resulting in disrupted homeostasis and infiltration of leukocytes, which correlates with the pathology and disease symptoms of NCC patients. Results In order to characterize the role of the ependymal barrier in the immunopathogenesis of NCC, we isolated ependymal cells using laser capture microdissection from mice infected or mock-infected with the closely related parasite Mesocestoides corti, and analyzed the genes that were differentially expressed using microarray analysis. The expression of 382 genes was altered. Immune response-related genes were verified by real-time RT-PCR. Ingenuity Pathway Analysis (IPA) software was used to analyze the biological significance of the differentially expressed genes, and revealed that genes known to participate in innate immune responses, antigen presentation and leukocyte infiltration were affected along with the genes involved in carbohydrate, lipid and small molecule biochemistry. Further, MHC class II molecules and chemokines, including CCL12, were found to be upregulated at the protein level using immunofluorescence microcopy. This is important, because these molecules are members of the most significant pathways by IPA analyses. Conclusion Thus, our study indicates that ependymal cells actively express immune mediators and likely contribute to the observed immunopathogenesis during infection. Of particular interest is the major upregulation of antigen presentation pathway-related genes and chemokines/cytokines. This could explain how the ependyma is a prominent source of leukocyte infiltration into ventricles through the disrupted ependymal lining by way of pial vessels present in the internal leptomeninges in murine NCC.